Knowledge-intensive of innovation project: measurement and controlfeatures - A. Galymkair (Хабаршысы. Экономика сериясы, 2016)
The article is devoted to the actual problem of providing intensive implemented innovative projects.The author explores the features and characteristics of management of innovative projects with predetermined quantitative and qualitative parameters of measure.On the basis of sum-marizing the various theoretical approaches to the definition of the phe-nomenon of R & D intensity, the author proposes to clarify the quantitative criteria that must be met at each stage of an innovative project to provide adequate research intensity of the final result of the project. In this regard, the article stresses the need to implement results-oriented management systems.